Software power estimation and optimization for high performance, 32-bit embedded processors - Russell, J.T.; Jacome, M.F. (Proceedings International Conference on Computer Design. VLSI in Computers and Processors (Cat. No.98CB36273), 1998)
A software energy estimation model is presented for a family of high performance, integrated, 32-bit embedded RISC processors. This model is significantly less complex than previous models, and yet is demonstrated to accurately predict energy consumption to within 8% with 99% confidence based on physical measurements. Factors such as operating frequency, source/destination registers, and operand values are explored. In view of this model, previously proposed optimizations are evaluated for potential energy savings. We conclude that, for the class of processors under discussion, a good optimizing compiler that minimizes execution time will simultaneously minimize energy consumption.